THE APPLICATION OF MOTION AND SONG IN IMPROVING THE ABILITY TO MEMORIZE ASMAUL HUSNA IN CHILDREN AGED 5-6 YEARS - Fitriani S, Shalsyabila; Wahyuni, Akhtim (Academic Journal Research, 2024)
Objective: This study aims to examine the effectiveness of the movement and song method in enhancing the memorization and understanding of Asmaul Husna in children aged 5–6 years. Methods: A qualitative descriptive approach was employed, with data collected through observations, interviews with principals, teachers, and students, and documentation. The research subjects included kindergarten students and educators at RA Darun Najah Sukodono. Data validity was ensured using triangulation techniques by combining information from various sources. Data analysis involved summarization, thematic identification, and presentation of findings. Results: The findings reveal that incorporating physical movement and singing into the learning process makes memorizing Asmaul Husna engaging and effective. This method actively involves children, enhances their emotional engagement, supports motor development, and improves their ability to understand the meaning of Asmaul Husna. Despite these benefits, challenges include time constraints and varying levels of parental support in reinforcing the method at home. Novelty: This study demonstrates the unique integration of movement and song as a fun, developmentally supportive, and culturally relevant approach to teaching religious content to early childhood learners. The method fosters better memorization and comprehension while addressing both cognitive and motor development.